Adult‐onset dominant muscular dystrophy in Greek families caused by Annexin A11. Issue 10 (22nd September 2022) - Johari, Mridul; Papadimas, George; Papadopoulos, Constantinos; Xirou, Sophia; Kanavaki, Aikaterini; Chrysanthou‐Piterou, Margarita; Rusanen, Salla; Savarese, Marco; Hackman, Peter; Udd, Bjarne
Abstract: Objective: Mutations in the prion‐like domain of RNA binding proteins cause dysfunctional stress responses and associated aggregate pathology in patients with neurogenic and myopathic phenotypes. Recently, mutations in ANXA11 have been reported in patients with amyotrophic lateral sclerosis and multisystem proteinopathy. Here we studied families with an autosomal dominant muscle disease caused by ANXA11 :c.118G > T;p.D40Y. Methods: We performed deep phenotyping and exome sequencing of patients from four large Greek families, including seven affected individuals with progressive muscle disease but no family history of multi‐organ involvement or ALS. Results: In our study, all patients presented with an autosomal dominant muscular dystrophy without any Paget disease of bone nor signs of frontotemporal dementia or Parkinson's disease. Histopathological analysis showed rimmed vacuoles with annexin A11 accumulations. Electron microscopy analysis showed myofibrillar abnormalities with disorganization of the sarcomeric structure and Z‐disc dissolution, and subsarcolemmal autophagic material with myeloid formations. Molecular genetic analysis revealed ANXA11 :c.118G > T;p.D40Y segregating with the phenotype. Interpretation: Although the pathogenic mechanisms associated with p.D40Y mutation in the prion‐like domain of Annexin A11 need to be further clarified, our study provides robust and clear genetic evidence to support the expansion of the phenotypic spectrum of ANXA11 .